2013
DOI: 10.1016/j.taap.2013.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of permanent loss of olfactory receptor neurons induced by the herbicide 2,6-dichlorobenzonitrile: Effects on stem cells and noninvolvement of acute induction of the inflammatory cytokine IL-6

Abstract: We explored the mechanisms underlying the differential effects of two olfactory toxicants, the herbicide 2,6-dichlorobenzonitrile (DCBN) and the anti-thyroid drug methimazole (MMZ), on olfactory receptor neuron (ORN) regeneration in mouse olfactory epithelium (OE). DCBN, but not MMZ, induced inflammation-like pathological changes in OE, and DCBN increased interleukin IL-6 levels in nasal-wash fluid to much greater magnitude and duration than did MMZ. At 24 h after DCBN injection, the population of horizontal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Another possible explanation is that OSNs in the regenerated OE were derived from residual GBCs, not from HBCs lacking IFT88. This is consistent with the MMI-induced lesion, which can leave residual GBCs (Xie et al, 2013). However, further studies involving lineage tracing are required to conclusively determine whether HBCs lacking cilia contribute to OE regeneration.…”
Section: Loss Of Cilia In Hbcs Results In the Improper Regeneration Osupporting
confidence: 79%
“…Another possible explanation is that OSNs in the regenerated OE were derived from residual GBCs, not from HBCs lacking IFT88. This is consistent with the MMI-induced lesion, which can leave residual GBCs (Xie et al, 2013). However, further studies involving lineage tracing are required to conclusively determine whether HBCs lacking cilia contribute to OE regeneration.…”
Section: Loss Of Cilia In Hbcs Results In the Improper Regeneration Osupporting
confidence: 79%
“…A number of pathways known to be active in the OE, including Wnt, Notch, and EGF, have been shown to affect p63 expression levels in other tissues (21,(43)(44)(45). Moreover, the environment at the time of activation can direct different outcomes, because very severe injury to the OE, worse than the damage occasioned by MeBr exposure here, causes spared HBCs to give rise to metaplastic respiratory epithelium rather than regenerating GBCs and restoring the OE (46). Further elucidation of the role of activating and quiescence-maintaining pathways and more detailed analysis of HBC expression profiles with and without epithelial injury will be necessary to use these cells in regenerative applications.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculation of toxicants into the IOI-transgenic mouse showed that TNF-α-induced inflammation lasted for 6 weeks and compromised the regeneration of OSNs, although the effect was not permanent, suggesting that TNF-α suppresses the proliferative activity of basal cells (12, 61). In contrast, intraperitoneal injection of the herbicide 2,6-dichlorobenzonitrile induced inflammation-like pathological changes in OE and depleted the horizontal basal cells, resulting in permanent loss of OSNs (62). A critical next step is to elucidate the molecular mechanisms underlying the specific loss of OSNs and the resistance of basal and sustentacular cells to olfactory inflammation.…”
Section: Discussionmentioning
confidence: 99%